Lessons to be Learned from the Inter-American Commission on Human Rights Concerning Precautionary Measures: A Blueprint for ASEAN - Chrisbiantoro, Chrisbiantoro; Yusuf, Hudi; Untoro, Utami Yustihasana (Riviera Publishing, 2025)
Regional or sub-regional institutions are a necessity in a modern legal system, considering that similar systems have long been established in Europe and Latin America. The two regional mechanisms provide an alternative for justice seekers at the national level who do not find justice and whose cases tend to meet exhausted local remedy, regional human rights bodies have an important role in promoting and protecting human rights because they are closer to the condition of the people. Specifically related to precautionary measures such as those in the Latin American mechanism, ASEAN sub-regional institutions must dare to build similar mechanisms so that serious and gross violations of law and human rights can be prevented. It is time for ASEAN sub-regional institutions to strengthen their presence in ensuring legal and human rights protection in the Region, one of which is through the precautionary measures mechanism to prevent potential legal and human rights cases from having a wider impact. The Inter-American human rights system is one of the best examples for ASEAN to learn from, because there are some similarities between ASEAN and Latin America. For example, both regions have had a history of dictatorship, suffered from the Cold War and nowadays are transitioning to democracy and progressing in promoting human rights.